A novel use of hyperfine structure in the electron paramagnetic resonance of interacting pairs of paramagnetic defects in diamond - Nadolinny, V; Yelisseyev, A; Baker, M; Newton, M; Twitchen, D; Hofstaetter, A; Feigelson, B (1999)
It is the hyperfine structure of N-14 and C-13 in the electron paramagnetic resonance (EPR) spectrum which indicates that the unpaired electron of a single substitutional nitrogen atom in diamond is in one of the four anti-bonding N-C orbitals. We show that, for diamonds containing a very high concentration of nitrogen, the hyperfine structure of interacting pairs of nitrogen atoms indicates that for close neighbours there are unique orientations of the constituent N-C bonds, while at larger distances the orientations are random.